Perlindungan Hukum Bagi Nelayan Sebagai Akibat Adanya Aktivitas Penambangan Pasir Laut Pada Proyek Reklamasi Makassar New Port (MNP) Sulawesi Selatan - Daffa Raihan Fadha’il; Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2024)
In this research regarding the sea sand mining case that occurred on Kodingareng Island, Makassar, South Sulawesi, there were 3 main subjects with a total of 15 sources for interviews consisting of 13 fishermen, 1 Head Director of the Makassar Legal Aid Institute, and 1 Head of the Legal Division of the Forum for the Environment. Indonesia, South Sulawesi. The purpose of this research is to find out the legal protection that fishermen get from the consequences of sea sand mining activities at the Makassar New Port (MNP) South Sulawesi reclamation project and to find out the criminal law enforcement that can be given to fishermen as victims of the consequences of sand mining activities. sea at the Makassar New Port (MNP) South Sulawesi reclamation project. This research was studied using empirical juridical research methods using qualitative descriptive data analysis techniques. The results of the research and conclusions are based on the existing problem formulation, that legal protection for Kodingareng Island fishermen as victims and criminal law enforcement against sea sand mining activities do not operate in accordance with existing laws and legal principles, so that the fishermen and the people of Kodingareng Island still feeling the impact and losses to this day.